2021
DOI: 10.3389/fpsyt.2021.661948
|View full text |Cite
|
Sign up to set email alerts
|

It's Not That Great Anymore: The Central Role of Defense Mechanisms in Grandiose and Vulnerable Narcissism

Abstract: Objectives: The concept of narcissism contains a yet unresolved paradox: Its grandiose facet depicts the psychopathological core but is often associated with life-satisfaction and overall functioning, whereas its vulnerable facet is associated with psychological distress, but still not included in the international classification systems. Our goal was to investigate the relationship between the two facets of narcissism expecting underlying defense mechanisms to be core elements. First, we aimed to identify def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 147 publications
(130 reference statements)
3
16
0
Order By: Relevance
“…Crossed-out items were removed because of a high overlap with the other listed item: Exhibitionism FFNI005 FFNI140; Grandiose Fantasy FFNI037 FFNI067; Indifference FFNI078 FFNI123; Lack of Empathy FFNI116 FFNI146; Manipulativeness FFNI053 FFNI098; Reactive Anger FFNI046 FFNI106 8 FFNI060 FFNI064 9 For comparability, we evaluated two-and three-factor models (though the optimization was based on the three-factor model) and used Maximum Likelihood estimation, as in Study 1. 10 See Kampe et al (2021) for a recent and fine-grained analysis of defense styles in narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…Crossed-out items were removed because of a high overlap with the other listed item: Exhibitionism FFNI005 FFNI140; Grandiose Fantasy FFNI037 FFNI067; Indifference FFNI078 FFNI123; Lack of Empathy FFNI116 FFNI146; Manipulativeness FFNI053 FFNI098; Reactive Anger FFNI046 FFNI106 8 FFNI060 FFNI064 9 For comparability, we evaluated two-and three-factor models (though the optimization was based on the three-factor model) and used Maximum Likelihood estimation, as in Study 1. 10 See Kampe et al (2021) for a recent and fine-grained analysis of defense styles in narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…Following Vaillant (1971) hierarchical approach, we used the German version of the Defense Style Questionnaire (DSQ-40; Schauenburg et al, 2007). The hierarchical assignment of defense mechanisms to respective scales of adaptiveness was in line with recent work (see Kampe et al, 2021, for a detailed assignment description; but also see Schauenburg et al, 2007, for a different approach). We also assessed emotion regulation difficulties and coping strategies deriving from explicit models of affect regulation.…”
Section: The Present Studymentioning
confidence: 99%
“…adaptive, intermediate, and maladaptive defense mechanisms (for the allocation of the items see also Kampe et al, 2021). Cronbach's α in the present study was α = .64 for the adaptive defense mechanisms, α = .57 for the intermediate defense mechanisms and α = .88 for the maladaptive defense mechanisms.…”
Section: Defense Mechanismsmentioning
confidence: 99%
“…Treatment studies have also demonstrated the change characteristics of defenses in relationship to clinical outcome variables. Despite their clinical importance and privileged position in psychodynamic models of psychopathology [5] and development, to our knowledge, no published study has investigated defense mechanisms in a large, general population sample.…”
Section: Introductionmentioning
confidence: 99%